2017
DOI: 10.1002/anie.201708921
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Reactions of CO2 and Indium‐Silylamides and Catalytic Synthesis of Ureas

Abstract: The indium compounds In(N(SiMe ) ) Cl⋅THF (2) and In(N(SiMe ) )Cl ⋅(THF) (3) were shown to react with CO to give [(Me Si) N)InX(μ-OSiMe )] (X=N(SiMe ) 4, Cl 5). 0.05-2.0 mol % of the species 3 acts as a pre-catalyst for the conversion of aryl and alkyl silylamines under CO (2-3 atm) to give the corresponding ureas in 70-99 % yields. A proposed mechanism is supported by experimental and computational data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 72 publications
2
26
0
1
Order By: Relevance
“…The 31 P{ 1 H} NMR spectrum of 2 showedasingle resonancea td = À1.5 ppm with coupling to the carbon of CO 2 of J = 19 Hz in the 13 C-labelled product. The geometry of 2 is similar to that seen in 1 with the newly formed PÀCa nd OÀBd istances being 1.8590 (14) and 1.4099(18) ,respectively. The 11 B{ 1 H} NMR spectroscopic data showedasingle resonance at 53.1 ppm.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The 31 P{ 1 H} NMR spectrum of 2 showedasingle resonancea td = À1.5 ppm with coupling to the carbon of CO 2 of J = 19 Hz in the 13 C-labelled product. The geometry of 2 is similar to that seen in 1 with the newly formed PÀCa nd OÀBd istances being 1.8590 (14) and 1.4099(18) ,respectively. The 11 B{ 1 H} NMR spectroscopic data showedasingle resonance at 53.1 ppm.…”
supporting
confidence: 53%
“…[4] In the intervening years, av ariety of B/N, [5] B/P, [6] Al/P, [7] and Si/P [5a, 8] systemsh ave been developed to capture or effect stoichiometric or catalytic reduction of CO 2 .A part from FLPs, basic main-group reagents have been exploited in reactionsw ith CO 2 .F or example, the carboxylations of N-heterocyclic carbenes [9] as well as silyl and germyl amides [10] have been reportedw hereas Dielmann and co-workers have described CO 2 captureb yh ighly basic phosphines incorporating imidazolin-2-ylidenamino substituents. [14] Interestingly, even thought he direct reactiono fC O 2 with amines [12c, 15] generally requires high pressure (14-140atm)a nd high temperature (130-170 8C), we have recently shown that judicious choiceo fs olventp romotes the reaction of CO 2 and silylamines to give silylcarbamates and ureas. [13] In 2018, we reportedi ndiumbased Lewis acid catalysts for the conversion of silylamines and CO 2 to ureas with liberation of silylethers.…”
mentioning
confidence: 99%
“…Stephan et al. have reported the synthesis of substituted ureas by direct reaction of CO 2 (2–3 atm pressure) with aryl and alkylsilylamines over indium amides as catalyst . Here the In complex reacts with the aryl/alkylsilylamines to form an intermediate complex.…”
Section: Catalytic Sites and Mechanistic Aspects Of Co2 Fixation Reacmentioning
confidence: 99%
“…have reported the synthesis of substituted ureas by direct reactiono fC O 2 (2-3 atm pressure) with aryl and alkylsilylamines over indiumamides as catalyst. [205] Here the In complex reacts with the aryl/alkylsilylamines to form an intermediate complex. This is followed by the insertion of CO 2 molecules into the InÀNb ond and reaction with silyl carbamate species to form the substituted ureas.…”
Section: Catalytic Sites and Mechanistic Aspects Of Co 2 Fixation Reamentioning
confidence: 99%
“…POV-ray depictionso fa)2 and b) 3.C:black, N: blue, Cl: green, O: red, Si:light-pink, In:r ed-brown [26]. Scheme 2.…”
mentioning
confidence: 99%